Structural controls of the migration of mantle-derived CO2 offshore in the Santos Basin (Southeastern Brazil) - Plawiak, Rafael André Belotto; Carvalho, Marcelo José; Sombra, Cristiano Leite; Brandão, Davy Raeder; Mepen, Michelle; Ferrari, André Luiz; Gambôa, Luiz Antônio Pierantoni (Frontiers in Earth Science, 2024)
We present a multi-scale conceptual model based on structural controls of the migration of mantle-derived CO2 offshore in the Santos Basin (Southeastern Brazil). We assembled the model from a regional 2D seismic reflection line integrated with potential gravimetric field data and a local 3D seismic reflection volume integrated with well data (lithologies and in situ stress). (i) The geochemical isotope range of δ13CCO2 falls mostly within −7‰ and −5‰ and shows relatively high values for 3He/4He represented by an R/Ra rate of up to 5.60, indicating CO2 mantle generation and degassing. (ii) Seismic interpretation feasibly validated by potential gravimetric responses of the crustal structure (Moho discontinuity) show CO2 migration through deep-seated faults in a region of highly stretched continental crust with oceanward mantle uprising. (iii) Early Cretaceous basement highs generated in an obliquely syn-rift faulting system control CO2 accumulation in thermogenic travertines (hydrothermal carbonate reservoirs of continental lakes), and Aptian evaporites subsequently trap it.